2018
DOI: 10.1016/j.eplepsyres.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in classic Rett syndrome: Course and characteristics in adult age

Abstract: Epilepsy continues to be a major concern in adults with RTT. Two thirds of women above 30 years of age remained with active epilepsy and 50% of them had seizures at least weekly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…This somewhat differs from our results, which may be due to the variability that exists in the population, especially when evaluating different age groups at different time points. The median age at seizure onset in our study was 4 years, which is consistent with previous reports of median age between 4 and 4.7 years 20,29,30 . Seizures types reported were similar to the data obtained in an Italian cohort, suggesting consistency across studies 20 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This somewhat differs from our results, which may be due to the variability that exists in the population, especially when evaluating different age groups at different time points. The median age at seizure onset in our study was 4 years, which is consistent with previous reports of median age between 4 and 4.7 years 20,29,30 . Seizures types reported were similar to the data obtained in an Italian cohort, suggesting consistency across studies 20 …”
Section: Discussionsupporting
confidence: 92%
“…The median age at seizure onset in our study was 4 years, which is consistent with previous reports of median age between 4 and 4.7 years. 20,29,30 Seizures types reported were similar to the data obtained in an Italian cohort, suggesting consistency across studies. 20 Compared to T-RTT, seizures in CDD are more severe and begin at a much younger age, consistent with CDD historically being associated with the early onset seizure RTT variant.…”
Section: Seizure Phenotypessupporting
confidence: 81%
“…For example, a recent large-scale study of 793 individuals reported that there were no significant associations between age of developmental regression and age of seizure onset in patients with RTT or in patients with so-called RTT-like disorders [ 42 ]. Thus, findings of the above correlative nature do not ascertain whether the epilepsy plays a crucial role in deteriorated cognitive abilities in RTT, or if it alternatively reflects the more severe underlying pathophysiology [ 105 ]. In support of the latter explanation, Cooper and colleagues reported that increases in EEG abnormalities and seizures follows developmental regression rather than precedes it in patients with RTT, thus reflecting the consequences of pathological processes that trigger the regression [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Comorbidities of epilepsy, breathing disturbances, and scoliosis are frequent and reported to occur in up to 90% (Henriksen et al, 2018), >95% (Tarquinio et al, 2018), and 75% (J. Downs, Torode, Wong, Ellaway, Elliott, Christodoulou, et al, 2016) of individuals with RTT.…”
mentioning
confidence: 99%